Teaching E-Kit for Foundation Topic - Awang Jepri, Dayang Afiqah; Mohamed, Maziana (Research and Innovation in Technical and Vocational Education and Training, 2022)
To attract students, teachers need to wisely select and plan the use of appropriate teaching aids in ensuring teaching and learning runs smoothly while strengthening students' knowledge. This study was conducted to develop a Teaching E-Kit for Foundation Topic in building construction course as a teaching aid. The ADDIE model was chosen as a guide in the development process of e-kit and the research instrument used was an expert evaluation form distributed to 3 experts who are experienced in the field of building construction. The findings show that the content is suitable and the teaching E-Kit for Foundation Topic can be used as a teaching aid. Overall, this e-kit was successfully developed, suitable for the foundation works module and can be used as teaching aids to instructors and students who take building construction course.